Bandwidth‐constrained digital pre‐compensation technique for multi‐carrier satellite communications. (21st April 2015) - Kelly, N.; Allegue‐Martínez, M.; Arapoglou, P.‐D.; Zhu, A.
Summary: A wide variety of imperfections impact end‐to‐end performance in multiple‐carrier per transponder transparent satellite links. Analysis of the link architecture leads to the identification of the sources and characteristics of distortion experienced by a typical multi‐carrier signal. This paper introduces a new remote pre‐compensation technique that takes this analysis into account to compensate for the specific distortion that occurs in the satellite channel. The proposed technique succeeds in compensating both linear and nonlinear channel distortions while overcoming the numerous challenges associated with remote waveform predistortion. Excellent linearisation performance has been observed across a wide range of link scenarios, even for high power amplifiers already linearised in the analogue domain. In addition, through an extensive end‐to‐end simulation campaign and a field programmable gate array implementation of the new algorithms, feasibility of the technique has been verified. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This paper introduces a new remote pre‐compensation solution for transparent satellite links based on techniques developed in terrestrial wireless communications. The proposed technique succeeds in compensating both linear and non‐linear channel distortions while overcoming the numerous challenges associated with remote waveform predistortion. Strong linearization performance is reported across a range of link scenarios, and feasibility is verified through extensive end‐to‐end simulation and FPGA implementation.